Enhanced Prepare2Excel: Its Effect on the Board Licensure Examination for Professional Teachers Reviewees - Villanueva, Emelyn; Dalisay, Alvin; Fabiala, Dana Kaye; Lachica, Alphee; Balderama, Cristina Marie M. Juanzo (Romblon State University Research Journal, 2023)
This study tested the effectiveness of the college-developed online review facility, Prepare2Excel. Primarily, it purported to provide enhanced learning-tool both for Board Licensure Examination for Professional Teachers (BLEPT) reviewers and facilitators; customize review programs based on the current reviewers’ needs; extend the reach of the review facilities beyond RSU premises; and achieve 100% rate of BLEPT passers. Reviewers’ scores in diagnostic, pre-board, and actual BLEPT test results were compared. The intervention was done through a series of sessions, and participants took the tests at the scheduled time as set by the college. Paired sample t-test was employed to test for significant differences between the three conditions. Interview was also conducted to supplement the quantitative data gathered. Based on the findings, the intervention was found to be helpful for the participants’ performance in BLEPT. With that, it is highly recommended for the BLEPT takers for the succeeding years. Most importantly, since this is technology-based, it is expected that data from each phase of the program can be secured well and organized for future reference, hence an ideal way for an effective data management system, which includes database management systems, data warehouses, data integration tools, analytics, and more.